Legislative Research: A specialised approach within legal research studies - Mishra, Babita (Samsad Journal संसद जर्नल, 2026)
In the modern legal system, statutes have become one of the primary sources of law, making legislative research essential for lawyers, judges, lawmakers, researchers, and policymakers. Legislative research is a vital aspect of legal research, as it connects statutory interpretation, policy analysis, and the legal system as a whole. Legislative research involves a distinct research methodology of identifying and locating statutes, tracing legislative history, interpreting statutory provisions, and comparative legislative research. This paper explores the methodology and role of legislative research in legal research, its theoretical basis, principles, and tools, its significance for legal professionals, and the possible challenges in Nepal. This paper identifies the best practices in legislative research with comparative analysis with countries such as the USA and the UK and provides suggestions on how legislative research can be made more accessible, reliable, and effective in influencing the legal process, which includes digitization and codification of law, improving legislative drafting standards, publication of legislative history and integration of legislative research into legal education. This paper concludes that legislative research is not merely a technical or academic exercise but also serves an important function in the law-making process and in good governance.